ANALISIS PERBANDINGAN PENETAPAN HAKIM TERHADAP DISPENSASI PERKAWINAN AKIBAT HAMIL DILUAR NIKAH - Ekasari Ekasari; Ema Fathimah; Gibtiah Gibtiah (Muqaranah, 2021)
Abstract One of the marriage dispensation cases that was granted by the Palembang Class IA religious court was assurance Number: 310/Pdt.P/2020/PA.PLG and what was rejected by the Banjarnegara religious court was assurance number: 66/Pdt.P/2019/PA.Ba. The interesting thing in this determination is the difference in the lawful fundamental for the consideration of the Palembang religious court judges in granting and the Banjarnegara religious court judges in rejecting the dispensation application submitted by the applicants. However, the substance of both is the same. The problem and goal of this inquire about is to discover out the basis in law, similarities and differences in the legal reason of the judge's thought of the two choices. This investigate may be a sort of normative juridical inquiry. The type of data used is qualitative data. Data analysis methods used are deductive and comparative methods. The results of the study show that the legal basis for the justice granting the application for dispensation for marriage is article 7 paragraph 2 of law number 1 of 1974 concerning marriage as revise by law number 16 of 2019, article 26 paragraph 1 letter a of law number 35 of 2014 concerning amendments to law number 23 of 2002 concerning child protection. In addition, the judge also uses the rules of fiqh, namely Saad al-Dzariah. The judge's legal basis for rejecting the application for a marriage dispensation is article 7 paragraph 1 of law number 1 of 1974 concerning marriage and article 1 number 1 of law number 35 of 2014 concerning amendments to law number 23 of 2002 concerning child protection. The similarity is that they both have the same substance. The difference is that the Palembang religious court judge granted it and the Banjarnegara religious court judge rejected the marriage dispensation application due to pregnancy out of wedlock. Keywords: Marriage, Dispensation, Marriage Age Limit